Proceso de adquisición de materiales para obras de la constructora Las Galias S.A. en Bogotá. (2023)
The argument analysis in the proposal, aimed at generating an optimal process in the acquisition of materials, was carried out based on the identification of shortcomings in the supply chain specifically in the warehouse and purchasing area of ​​the company's fronts or projects. . Therefore, efficient management in the supply chain understood in three processes: supply, production and distribution is defined from an ideal approach for the healthy growth of companies in a multifaceted market. The supply of the necessary materials, resources or inputs during the phases of the works allows the life cycle of the projects to be developed under the focus of fruitful work, this allows us to understand that, depending on the area of ​​analysis, the process may have particularities. that make activities relatively simple or complex.